2020
DOI: 10.5624/isd.2020.50.2.99
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular calcifications of the temporomandibular joint and associations with degenerative bone alterations

Abstract: Purpose: The purpose of this study was to use cone-beam computed tomography (CBCT) images to determine the prevalence of calcifications in the temporomandibular joint (TMJ) and to evaluate any associations between the presence of such calcifications and degenerative bone alterations of the TMJ, sex, or age. Materials and Methods: In this retrospective study, 1,058 CBCT exams were analyzed, and data regarding the presence and quantity of calcifications, the affected side, any degenerative alterations of the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…In the present study, 62.5% of all TMJ calcifications were in females although this relationship did not reach statistical significance. Our data support the findings of Almeida et al who reported the presence of unilateral TMJ calcifications that were correlated with age but not gender [15].…”
Section: Calcifications In Joint-related Diseasessupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, 62.5% of all TMJ calcifications were in females although this relationship did not reach statistical significance. Our data support the findings of Almeida et al who reported the presence of unilateral TMJ calcifications that were correlated with age but not gender [15].…”
Section: Calcifications In Joint-related Diseasessupporting
confidence: 93%
“…Various studies suggest the presence of a gender and age bias in the development of calcifications [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. In agreement with previous CBCT and PR studies [24,25,30], we found STCs to be related to both age and gender; however, our data was in contrast to the CBCT results of Misias et al [27].…”
Section: Most Common Type Of Calcification In Pwc Gender-age Comparis...supporting
confidence: 87%
See 1 more Smart Citation
“…Degenerative changes in articular bone, cartilage, and discs can be detected by MRI. Although CT has higher specificity and sensitivity than MRI in the diagnosis of bone changes, Liu et al found the accuracy of MRI in determining the location, morphology and evaluation of intervertebral discs [ 11 ]. The diagnosis of osteoarthritis should be based on the evaluation of MRI images in combination with clinical examination.…”
Section: Discussionmentioning
confidence: 99%